EFEKTIVITAS METODE MATERNAL REFLEKTIF (MMR) DALAM MENINGKATKAN KEMAMPUAN MENYUSUN STRUKTUR KALIMAT PADA ANAK TUNARUNGU DI SLB BINA NUSANTARA - Ega Yuristia Wahyuni, - (2020)
Hearing impairment children have obstacles in constructing sentence structures. The sentence structure pattern of their writing is incorrect so that it affects their visual or written expressive language skills which caused the other person to misinterpret the message. Therefore, their ability to structure sentences should be improved by checking on their needs with optimizing their visual senses, involving them interactively in learning, and applying a method that can relate language structure to the context of events. To find out the enhancement of their ability in constructing sentence structure, the researcher used the language learning method, namely MMR, to fifth class hearing impairment children of SDLB. This research obtained pre-experimental with One Group Pretest-Posttest Design. Five students were chosen as the sample of this research. The instrument applied was a written test. The result of data processing and data analysis showed that the maternal reflective method improved the ability to construct sentence structure for fifth class hearing impairment children of SLDB at SLB Bina Nusantara. It could be seen from the increase of their pre-test and post-test scores. In conclusion, the researcher recommends the hearing impairment teachers use the Maternal Reflective Method (MMR) as an alternative to improve the ability to construct sentence structure for hearing impairment children. Keywords: Language Learning Method. Maternal Reflective Method (MMR). Constructing Sentence Structure. Hearing Impairment Children.